2014
DOI: 10.1098/rstb.2013.0185
|View full text |Cite
|
Sign up to set email alerts
|

Action observation treatment: a novel tool in neurorehabilitation

Abstract: This review focuses on a novel rehabilitation approach known as action observation treatment (AOT). It is now a well-accepted notion in neurophysiology that the observation of actions performed by others activates in the perceiver the same neural structures responsible for the actual execution of those same actions. Areas endowed with this action observation-action execution matching mechanism are defined as the mirror neuron system. AOT exploits this neurophysiological mechanism for the recovery of motor impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
221
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(241 citation statements)
references
References 68 publications
4
221
0
16
Order By: Relevance
“…As described above, motor imagery is influenced by the environment, personal imaging ability, and mental effort. In contrast, action observation is easier to apply, despite activation of the same neural network as motor imagery [43]. In addition, Conson et al revealed that action observation had an effect of promoting motor imagery [44].…”
Section: Application Of Motor Imagery and Action Observation To Physimentioning
confidence: 99%
“…As described above, motor imagery is influenced by the environment, personal imaging ability, and mental effort. In contrast, action observation is easier to apply, despite activation of the same neural network as motor imagery [43]. In addition, Conson et al revealed that action observation had an effect of promoting motor imagery [44].…”
Section: Application Of Motor Imagery and Action Observation To Physimentioning
confidence: 99%
“…Motor imagery is influenced by the environment and personal imaging ability and requires mental effort. In contrast, action observation is easier to apply than motor imagery, despite targeting activation of the same neural network as motor imagery [35]. We have also reported that the left sensorimotor and parietal areas of the high-motor learning group showed a greater decrease in the alpha-2 and beta-2 rhythms than those of the lowmotor learning group during observation and execution.…”
Section: Action Observation and Motor Learningmentioning
confidence: 75%
“…Most of the actions that have been employed in AOT studies consist of upper limb transitive actions (i.e., actions with object interaction, e.g., using a pencil). These are usually daily actions that have been selected on the basis of their ecological value [27]. This kind of action has been shown to have increased MNS activity in neuroimaging studies [15,28] and corticospinal facilitation in transcranial magnetic stimulation (TMS) [29,30].…”
Section: Which Actions Should Be Used In Aot?mentioning
confidence: 99%